IMPACT OF HOLTEKAMP BRIDGE CONSTRUCTION ON DISASTER MITIGATION IN JAYAPURA’S COASTAL ZONE, PAPUA - Vidia Caroline Siauwke Pekpekai; Paulus Bawole; Wiyatiningsih; Winarna (Journal of Architecture & Environment, 2025)
Coastal areas are increasingly under pressure from various activities and natural phenomena. The construction of the Holtekamp Bridge in Jayapura has made Holtekamp Beach increasingly attractive as a trade and service area. However, these activities also increase the risk of disasters and affect the community's preparedness to deal with disasters. This article is the result of a descriptive qualitative study showing that the construction of the bridge has influenced the level of disaster mitigation both structural and non-structural at Holtekamp Beach. The novelty of this research article is to explore disaster mitigation in a coastal area in which settlement and business areas grow simultaneously. However, the existing mitigation measures are still uneven between the coastal area and the commercial area at Holtekamp Beach. Therefore, Holtekamp Beach needs to enhance disaster mitigation measures that are responsive to the area as a commercia